MODERN METHODS OF LAND MANAGEMENT DESIGN IN LAND MANAGEMENT FOR SPATIAL DEVELOPMENT OF TERRITORIAL COMMUNITIES - Mamonov К.; Shterndok Е.; Kasyanov, V.; Palamar А. (Municipal economy of cities (Technical science), 2025)
It is proven that changes are observed in the land management system, which are due to integration processes into European institutions. In this context, the formation and implementation of a land administration system is of particular importance, for the implementation of which modern methods of land management planning are used, and the improvement of the system for creating land management support is of particular importance. The topic of the study is relevant and timely for the development of land relations of territorial communities, increasing the efficiency of their land use. The goal of the study was achieved in terms of substantiating modern methods of land management planning in land management for the spatial development of territorial communities. The following tasks were solved in the study: substantiating theoretical provisions on determining modern methods of land management planning in land management; characterizing the spatial development of territorial communities, taking into account the directions and features of the application of modern methods of land management planning. As a result of the study, modern methods of land management planning in land management were determined to ensure the spatial development of territorial communities. The presented methods are of a comprehensive nature, covering functional, analytical, spatial aspects of territories, regulatory and legal support, project activities. The proposed directions for ensuring the geospatial development of territorial communities, where information and spatial support, assessment procedures, methods of land management design, mathematical modeling and forecasting, the use of geoinformation systems to determine ways to ensure spatial development, are of particular importance. The identified directions for ensuring geospatial development allow improving the system for developing comprehensive plans for the spatial development of territorial communities.